STRATEGI MANAJEMEN DALAM PROSES PENGEMBANGAN SUMBER DAYA MANUSIA PADA MASA PANDEMI COVID-19 (Studi Kasus: PT. Pan Brothers, TBK) - Yuni Tanti Seven Purba, (2021)
This study contains the company management strategy of PT Pan Brothers, Tbk in the process of developing human resources during the COVID-19 pandemic. The process of developing human resources during a pandemic is carried out by the company thats like recruitment, training, controlling, performance appraisal and evaluation without layoffs. This research method uses qualitative research methods with a case study approach. This study uses primary data obtained directly from informants namely assistant company managers, company labor unions and HR consultants. The results showed that implementation of the human resource development process carried out by companies during the pandemic was not much different from the development of human resources before the pandemic, only the process mechanism was different. The company provides applications or systems to facilitate the process of developing human resources during the COVID-19 pandemic by utilizing technology in the industrial revolution 4.0. Researchers also found that during the pandemic, employee loyalty was needed as mentioned by Malayu and Armstrong so that an integrated relationship was created between the company and employees in the process of developing human resources.